Leuconostoc lactis: An unusual cause for bacteremia - Bichitrananda Swain; Kundan Kumar Sahu; Subhrajita Rout (Wolters Kluwer Medknow Publications, 2015)
Leuconostoc species, the common saprophytic bacteria are now emerging as one of the important opportunistic pathogens. There are different risk factors such as compromised immunity, use of vancomycin, parenteral nutrition, and contaminated surgical implanted devices to contribute the human infection. We here present one of the unusual fatal cases of bacteremia in a cancer patient who was infected with a vancomycin-resistant strain of L. lactis.